Edukasi Peran Suami dalam Mengurangi Kecemasan Istri Saat Persalinan - Endang Sari; Mekar Zenni Radhia; Hanifa Zaini; Rahmatul Ulya; Elwitri Silvia; Rahmi Ramadhan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Maternal anxiety during the childbirth process is a common psychological condition that can potentially increase the risk of complications, prolong labor, and reduce the likelihood of a positive birthing experience. High anxiety levels in mothers may interfere with the effectiveness of labor, impact maternal and fetal well-being, and lead to increased medical interventions. One of the most important support systems during labor is the presence and active involvement of the husband. The husband’s role is not only limited to being present but also includes providing emotional, physical, and motivational support to the mother. Recognizing the importance of this role, this community service program was designed to enhance husbands’ understanding and skills in supporting their wives during childbirth, thereby helping to reduce maternal anxiety.The program consisted of several stages, including the delivery of structured health education sessions on maternal needs during labor, demonstrations of effective communication techniques, simulations of support during different stages of childbirth, and interactive discussions to address questions and share experiences. Through these activities, participants were encouraged to build empathy, strengthen their knowledge about labor, and develop the confidence to assist their wives effectively. The results of the program indicated a noticeable improvement in the husbands’ awareness of the importance of their role, as well as increased confidence in providing both emotional reassurance and physical assistance. Participants reported feeling better prepared to accompany their wives, manage unexpected situations, and foster a more supportive environment during childbirth. This initiative highlights the significant impact that targeted education and training for husbands can have on maternal psychological well-being, ultimately contributing to safer and more positive birth experiences.